Preventing musculoskeletal disorders due to manual material handling in the production process of clean water - Lady, Lovely; Nuraeni, Sekar Fani (Journal Industrial Servicess, 2024)
Several activities have been identified that can cause occupational diseases in the production process of clean water. The Minister of Manpower Regulation of Indonesia No.5 in 2018 emphasized the dangers of ergonomic factors in the workplace and efforts to control them. The hazards from ergonomic factors identified in the study are Manual Material Handling (MMH) and physical environmental hazards. The MMH assessment calculates the value of the Recommended Weight Limit (RWL) and Lifting Index (LI), and assesses the calories spent when lifting weights upstairs in the clean water production process. In the assessment of environmental hazards, potential hazards are predominantly caused by chemical substances used in the production process. The analysis was carried out using a hazard matrix and assessing the risk level of each hazard, as well as providing risk control recommendations to reduce potential work accidents. The control for extreme-level risks in the production division involves substituting manual handling (MMH) activities and substituting MMH by applying a mechanical system using a chemical dosing pump. Control of potential hazards from chemical substances includes using gloves, earplugs, and safety goggles. Improving work processes with mechanical processes and using personal protective equipment can minimize the potential for work-related injuries.